Electrodeposition of nanowires of a high copper content thiourea precursor of copper sulfide. Issue 55 (7th October 2019) - Sarma, Abhisakh; Dippel, Ann-Christin; Gutowski, Olof; Etter, Martin; Lippmann, Milena; Seeck, Oliver; Manna, Gouranga; Sanyal, Milan K.; Keller, Thomas F.; Kulkarni, Satishkumar; Guha, Puspendu; Satyam, Parlapali V.; et al.
Abstract : In this study we reported the pulsed electrodeposition technique of copper thiourea complex nanowires which is an important material class for application as a precursor of copper sulfide nanocrystals with potential use in solar cells, optoelectronics, medicine, etc. Abstract : Copper thiourea complexes are an important material class for application as a precursor of copper sulfide nanocrystals with potential use in solar cells, optoelectronics, medicine, etc. They represent a type of single source precursor, comprising both copper and sulfur in one chemical compound, whose tunable stoichiometry and morphology enable control of the quality and properties of the synthesized copper sulfide nanocrystals. Here, we present a template free electrochemical route to prepare nanowires of copper thiourea (tu) chloride hemihydrate ([Cu(tu)]Cl·½H2 O) by pulse deposition. We proposed the model of the growth of nanowires. We also demonstrate complete transformation from the precursor to copper sulfide nanowire by heating it to 180 °C that involves 20% volume loss due to the decomposition of organic constituents; the obtained nanowires have around 38% covellite (CuS) and 62% digenite (Cu1.8 S) phases. Electrochemistry offers the advantage of spatially selected deposition e.g. in the active regions of a device.